2024
DOI: 10.1021/acs.jafc.3c08362
|View full text |Cite
|
Sign up to set email alerts
|

Advancing High-Throughput MS-Based Protein Quantification: A Case Study on Quantifying 10 Major Food Allergens by LC-MS/MS Using a One-Sample Multipoint External Calibration Curve

Shupeng Yang,
Haopeng Lin,
Peijie Yang
et al.

Abstract: The LC-MS-based method has emerged as the preferred approach for quantifying food allergens. However, the preparation of a traditional calibration curve (MSCC) is labor-intensive and error-prone. Here, a sensitive and robust LC-MS/MS method for quantifying 10 major food allergens was developed and validated, where the one-sample multipoint external calibration curve (OSCC) was employed instead of MSCC. By employing the multiple isotopologue reaction monitoring (MIRM) technique with only one spiked level in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…To overcome these disadvantages, various methods for analysing food allergens using high-performance liquid chromatography–tandem quadrupole mass spectrometry (LC-MS/MS) have recently been developed ( Fallahbaghery, Zou, Byrne, Howitt, & Colgrave, 2017 ; Schalk, Koehler, & Scherf, 2018 ; Croote, Braslavsky, & Quake, 2019 ; Henrottin et al, 2023 ; Lexhaller, Colgrave, & Scherf, 2019 ; Huang, Zhu, Feng, Zhang, & Zhang, 2020 ; Ma et al, 2020 ; Ramachandran, Yang, & Downs, 2020 ; Wang et al, 2021 ; Xiong, Parker, Boo, & Fielder, 2021 ; Li et al, 2022 ; Neils, Broadbent, Bose, Anderson, & Colgrave, 2022 ; Henrottin et al, 2023 ; Yang et al, 2024 ). Our research group has also previously reported on methods for simultaneous detection of wheat and buckwheat ( Seki et al, 2021 ), or walnut and almond ( Torii et al, 2023 ) in processed foods using LC-MS/MS.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these disadvantages, various methods for analysing food allergens using high-performance liquid chromatography–tandem quadrupole mass spectrometry (LC-MS/MS) have recently been developed ( Fallahbaghery, Zou, Byrne, Howitt, & Colgrave, 2017 ; Schalk, Koehler, & Scherf, 2018 ; Croote, Braslavsky, & Quake, 2019 ; Henrottin et al, 2023 ; Lexhaller, Colgrave, & Scherf, 2019 ; Huang, Zhu, Feng, Zhang, & Zhang, 2020 ; Ma et al, 2020 ; Ramachandran, Yang, & Downs, 2020 ; Wang et al, 2021 ; Xiong, Parker, Boo, & Fielder, 2021 ; Li et al, 2022 ; Neils, Broadbent, Bose, Anderson, & Colgrave, 2022 ; Henrottin et al, 2023 ; Yang et al, 2024 ). Our research group has also previously reported on methods for simultaneous detection of wheat and buckwheat ( Seki et al, 2021 ), or walnut and almond ( Torii et al, 2023 ) in processed foods using LC-MS/MS.…”
Section: Introductionmentioning
confidence: 99%